The lipid profile as a marker for predicting the severity of dengue fever - K., Ravi; N., Keerthi Kumar; Malagi, Aishwarya D. (International Journal of Advances in Medicine, 2021)
Background: Dengue fever is a mosquito-borne viral disease. WHO currently estimates 390 million dengue infections annually worldwide. In India between 2015 to 2020, out of 7,08,783 cases about 1,144 deaths have been reported according to National vector borne disease control programme data. This study aims at evaluating the changes in lipid profile among dengue patients with relation to severity and complications. Methods: It is a cross sectional observational study conducted on 200 patients. The dengue patients were grouped according to WHO classification. The lipid profile was estimated and changes in its parameters were correlated with severity of dengue infection. Results: The age distribution in our study was between 18 to 65 years with mean age of 28.5±9.2 years. As per WHO 2009 criteria out of 200 patients, 120 (60%) were dengue without warning signs, 68 (34%) were dengue with warning signs and 12 (6%) were severe dengue. There was decreased total cholesterol, LDL-C, HDL-C found in all forms of dengue and statistically significant (p<0.05) lowest levels noted in patients with severe disease according to ANOVA test. Correlation analysis showed a significant negative correlation between LDL-C (r=-0.716), HDL-C (r=-0.657) and total cholesterol(r=-0.621) with relation to severity of dengue (p<0.05). Conclusions: Results of this study showed serum cholesterol levels are important correlates of dengue pathophysiology and severity and these may be used as a marker for predicting the severity of dengue fever.